A case report of harlequin ichthyosis with a favorable outcome: Early treatment and significant recovery - gholamreza faal; fatemeh rabani; Mahdi Hosseini (Tehran University of Medical Sciences, 2019)
Harlequin ichthyosis is the most severe form of autosomal-recessive congenital ichthyoses with a high mortality rate. In affected infants, mutations occur in the ABCA12 gene. The ABCA12 gene produces the proteins that are essential for the natural development of skin cells. In this disease, disruption in keratinization of epidermis results in the impaired barrier function and susceptibility of the neonate to dehydration and infection. Recent advances in neonatal care and early administration of treatment have increased the chances of child survival. In this article, we introduced a term female neonate with harlequin ichthyosis, born of a 26-year-old mother, significantly recovered by early treatment using an ointment (composed of Eucerin 88 g, sodium chloride 6 g, and urea 6 g).